2003
DOI: 10.2166/wst.2003.0110
|View full text |Cite
|
Sign up to set email alerts
|

Automation in sludge dewatering by novel on-line characterisation of flocculation

Abstract: A novel on-line method and system for characterisation of sludge flocs in view of improving sludge dewatering has been developed. The characterisation of sludge flocs was carried out after the conditioning or the flocculation process. The system uses a conventional CCD-line scan camera providing an on-line monitoring of the relative floc size distribution by image processing procedures. The image processing procedure has been re-evaluated and adapted to the practical dewatering results, obtained from a chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Narayanan et al (2003) recommended the use of dispersed instead of total Nocardiaform counts for process control purposes since they found that that dispersed Nocardiaform filaments, generated in large quantities by the release of floc-bound Nocardiaform filaments during deflocculation caused by non-ionic surfactants, were directly related to the amount of foaming observed in ASP plants. To correlate floc distribution to degree of dewatering from a pilot filter press, Sievers et al (2003) used a sensor based on image processing of a conventional line scan camera's output in order to derive the particle size distribution of sludge particles above 50 microns. They developed a correlation (n = 24, R 2 = 0.92) between a dimensionless factor summarizing the size distribution and output-to-input solids concentrations ratio.…”
Section: Instrumentation and Measurementsmentioning
confidence: 99%
“…Narayanan et al (2003) recommended the use of dispersed instead of total Nocardiaform counts for process control purposes since they found that that dispersed Nocardiaform filaments, generated in large quantities by the release of floc-bound Nocardiaform filaments during deflocculation caused by non-ionic surfactants, were directly related to the amount of foaming observed in ASP plants. To correlate floc distribution to degree of dewatering from a pilot filter press, Sievers et al (2003) used a sensor based on image processing of a conventional line scan camera's output in order to derive the particle size distribution of sludge particles above 50 microns. They developed a correlation (n = 24, R 2 = 0.92) between a dimensionless factor summarizing the size distribution and output-to-input solids concentrations ratio.…”
Section: Instrumentation and Measurementsmentioning
confidence: 99%
“…Coagulation/flocculation can effectively agglomerate sludge colloids to form large flocs through charge neutralization and bridging flocculation effects, is beneficial to sludge sedimentation, filtration and permeability, and is thus one of the most commonly used sludge conditionings in practical operation 15 17 . The employed coagulants/flocculants are of great significance in coagulation/flocculation 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, pelleted aggregates are difficult to control due to the fluctuations of sludge and wastewater both in flow rate and quality. A better understanding of hydrodynamic effects on development of layered pellet structure of aggregates is needed.METHODSBased on previous prototypes(Schroeder 2001;Sievers et al 2003), a bench scale replica of the FlocFormer system has been constructed(Stoll 2007) and installed in the municipal wastewater treatment plant "Zweckverband Klä rwerk Steinhä ule" (ZVK) located in Neu-Ulm, Germany. For the Model of pelleting flocculation(Ay 2004).…”
mentioning
confidence: 99%
“…The main principle of the Floc-analyser is described in more detail bySievers et al (2003). By means of this optical measuring system, the sludge is automatically scanned and evaluated on-line.…”
mentioning
confidence: 99%